Synthesis Of Open-Shell Iron Oxide-Polyelectrolyte-Silica Nanocomposite For Water Treatment Application - Che, Hui Xin (2017)
A open shell structure of silica-polyelectrolyte-iron oxide nanocomposite is synthesized via layer-by-layer assembly. Here, silica colloid is synthesized by Stöber process and iron oxide nanoparticles (IONPs) is synthesized by co-precipitation method. The successful assembly of silica, polyelectrolyte and IONPs into unified nanocomposite was monitored with dynamic light scattering (DLS) and electrophoretic mobility. The core-shell morphology of the nanocomposite was confirmed under the examination of Transmission Electron Microscope (TEM). The final structure showed good colloidal stability up to 10 hours under the monitoring of DLS. The nanocomposite was more magnetically responsive than the bare IONPs with shorten collection time after their exposure to low magnetic field gradient. The interfacial phenomena, which is the conformation of the particles-polymeric structure was monitored by Quartz Crystal Microbalance with Dissipation (QCM-D). The loosely bound and flexible nature of polyelectrolyte promoted larger IONPs deposited amount compared to the bare silica surface without a pre-adsorbed polyelectrolyte. Increasing the initial IONPs concentration (20 to 500 ppm) suppressed the polyelectrolyte layer, giving rise to a stiffer particles-polymeric structure. By increasing the solution ionic strength (0.1 to 100 mM) within critical coagulation concentration up to 50 mM NaCl (obtained by DLS and Derjaguin-Landau-Verwey-Overbeek theory), the particles-polymeric structure became more flexible, leading to the greater amount of deposited IONPs. The open shell structure of the nanocomposite was varied with different polyelectrolyte hierarchy, nature and architecture. From DLS, QCM-D, TEM and AFM (Atomic Force Microscope), it was observed that the deposition of greater amount of IONPs and pollutants molecules into polymeric network was attributed by: (1) the flexible structure conserved by the single layer rather than multilayers of polyelectrolyte, (2) the more extended structure constructed by higher molecular weight than the lower molecular weight of polyelectrolyte, and (3) the branched chain compared to linear chain of polyelectrolyte. Mean field and scaling approximations showed that the protruding side chains of branched PEI contributed to the thicker adsorbed layer (16.14 nm) with more ramified structure compared to linear PDDA (0.19 nm). By taking cationic Methylene Blue, anionic Methyl Orange dyes and Amoxicillin antibiotic as the model system, the performance of nanocomposite can be compared with the silica, silica-polyelectrolyte and bare IONPs. With the ability to facilitate Fenton and Fenton-like reaction with the presence of hydrogen peroxide, nanocomposite achieved highest pollutant removal efficiency among the synthesized nanoparticles. The easiness of magnetic recollection enabled nanocomposite to be recycled for subsequent pollutant removal runs. Nanocomposite retained high pollutant removal efficiency for total 5 recycled runs without significant dissolution of the IONPs from the nanocomposite. The pollutant removal process by nanocomposite can be well illustrated using Langmuir isotherm and pseudo-second-order kinetic model.